Writing the revolution : the construction of "1968" in Germany - Cornils, Ingo 1958- (Studies in German literature, linguistics, and culture, 2016)
In Germany, the concept of "1968" is enduring and synonymous with the German Student Movement, and is viewed, variously, as a fundamental liberalization, a myth, a second foundation, or an irritation. The movement's aims-radical re-imagination of the political and economic order and social hierarchy-have been understood as requiring a "long march." While the movement has been judged at best a "successful failure," cultural elites continue to engage in the construction of 1968. Ingo Cornils's book argues that writing about 1968 in Germany is no longer about the historical events or the specific objectives of a bygone counterculture, but is instead a moral touchstone, a marker of social group identity meant to keep alive (or at bay) a utopian agenda that continues to fire the imagination. The book demonstrates that the representation of 1968 as a "foundational myth" suits the needs of a number of surprisingly heterogeneous groups, and that even attempts to deconstruct the myth strengthen it. Cornils brings together for the first time the historical, literary, and media representations of the movement, showing the motivation behind and effect of almost five decades of writing about 1968. In so doing, Cornils challenges the way 1968 has been instrumentalized: as a powerful imaginary that has colonized every aspect of life in Germany, and as symbolic capital in cultural and political debates